"Talk to Her": Courtship politics Behind the Taiwanese Aboriginal Jaw's Harp - Szhr Ee Tan, (Wacana Seni Journal of Arts Discourse, 2003)
THE AMIS TELEPHONETHERE is an old, pseudo-romantic tradition among the Amis aborigines of Eastern Taiwan, involving a bamboo jaw's harp called the datok.